M2 Polarization of Monocytes-Macrophages Is a Hallmark of Indian Post Kala-Azar Dermal Leishmaniasis. - Debanjan Mukhopadhyay; Shibabrata Mukherjee; Susmita Roy; Jane E Dalton; Sunanda Kundu; Avijit Sarkar; Nilay K Das; Paul M Kaye; Mitali Chatterjee (Public Library of Science (PLoS), 2015)
The high level of functional diversity and plasticity in monocytes/macrophages has been defined within in vitro systems as M1 (classically activated), M2 (alternatively activated) and deactivated macrophages, of which the latter two subtypes are associated with suppression of cell mediated immunity, that confers susceptibility to intracellular infection. Although the Leishmania parasite modulates macrophage functions to ensure its survival, what remains an unanswered yet pertinent question is whether these macrophages are deactivated or alternatively activated. This study aimed to characterize the functional plasticity and polarization of monocytes/macrophages and delineate their importance in the immunopathogenesis of Post kala-azar dermal leishmaniasis (PKDL), a chronic dermatosis of human leishmaniasis. Monocytes from PKDL patients showed a decreased expression of TLR-2/4, along with an attenuated generation of reactive oxidative/nitrosative species. At disease presentation, an increased mRNA expression of classical M2 markers CD206, ARG1 and PPARG in monocytes and lesional macrophages indicated M2 polarization of macrophages which was corroborated by increased expression of CD206 and arginase-1. Furthermore, altered vitamin D signaling was a key feature in PKDL, as disease presentation was associated with raised plasma levels of monohydroxylated vitamin D3 and vitamin D3- associated genes, features of M2 polarization. Taken together, in PKDL, monocyte/macrophage subsets appear to be alternatively activated, a phenotype that might sustain disease chronicity. Importantly, repolarization of these monocytes to M1 by antileishmanial drugs suggests that switching from M2 to M1 phenotype might represent a therapeutic opportunity, worthy of future pharmacological consideration.